INVESTIGATION OF THE PRESENCE OF CHROMIUM (Cr) IN THE POULTRY FEED, CHICKEN MEAT AND EGG IN BANGLADESH USING LASER INDUCED BREAKDOWN SPECTROSCOPY TECHNIQUE: N. ASHRAFI, ISHTIAQUE. M. SYED, M. WAHADOSZAMEN (Bangladesh Journal of Physics, 2020)
Laser induced breakdown spectroscopy (LIBS) is a rapid, efficient and versatile atomic emission based elemental analysis technique. The existence of the toxic element Chromium (Cr), has been detected and quantified in this study using LIBS technique in biological samples such as poultry feed, chicken meat and egg collected from different local markets of Dhaka city. The analysis of LIBS spectra revealed along with Cr there were other elements such as Fe, Ca, Mg, Na, N, Zn, H, C, O, S, Be, B, P, Al, K, Co, Cu, Ni and Pb in all the samples under investigation. The quantitative analysis shows that the average concentration of Cr in the poultry feed, chicken meat and egg (yolk part) are 13.903%, 8.176%, and 12.261% with respect to Fe present in those samples respectively. To the best of our knowledge, this is the first time Cr is investigated in the biological samples using LIBS in Bangladesh.